Logistics Center Location Optimisation in Thrace: A Hybrid Approach Using AHP and TOPSIS Methods - Oguztimur, Senay; Kilicarslan, Gizem Nur; Alici, Ecem; Serdengecti, Kamil (KARE PUBL, 2023)
The region of Thrace, its proximity to Istanbul, the strong indus -trial infrastructure, and road transport in the region, due to the fact that our country is the gateway to Europe, are subject to strong mobility of loads. The load transport facilities in the area have an imbalanced relationship with one another. Unplanned and uncontrolled development of logistical components compromises logistical performance and jeopardizes the region's planned integ-rity. As a result of similar failures with living industrial towns, lo-gistics villages have been created. The purpose of this paper is to choose the best location for the envisaged logistics community in Thrace. The location of the logistics village should be chosen us-ing a system that is affordable, simple to grasp, quick, qualitative, adaptable, and universal. This model was developed by combining data from field research and book reviews at the same time. Ac-cording to the literature review, the two most preferred meth-ods for multi-criteria decision-making in logistics center siting are AHP and TOPSIS. Based on this data, our study provides a com-parative interpretation of these methods. Literature In addition to the survey, a field study was conducted, site selection criteria, in-depth interviews with experts on sub-criteria, and options were developed. The criteria of accessibility, costs, land characteristics, and social benefit criteria were taken into account. Tekirdag, cerkezkoy, Marmara Ereglisi, and Havsa were identified as op-tions. The results of the study showed that the AHP and TOPSIS applications provided consistent and uniform results.
Keywords: AHP; logistics center; multiple criteria decision making; TOPSIS; Thrace; ANALYTIC HIERARCHY PROCESS; MULTICRITERIA DECISION-MAKING; FUZZY-AHP; SELECTION; EXTENSION; SET; Public Administration